A Hospital Information System Application May Facilitate Staff Compliance with Quality Protocols in a Medical Unit: A Case Study - Karampela I; Tzortzis, E; Nikolopoulos, M; Dalamaga, M; Diomidous, M; Armaganidis, A. (Stud Health Technol Inform., 2018)
Quality standards have been widely adopted in healthcare, while the Hospital Information Systems (HIS) support quality management in modern hospitals. However, staff compliance lags behind. In this study, we investigated the effect of a novel application, implemented in the HIS, on staff compliance in the Intensive Care Unit of a tertiary teaching hospital. This application integrates quality protocols to the HIS, which is routinely used by the nursing staff. Demographic data and self-reported compliance were recorded before and after the intervention. We found that the compliance rate was significantly increased and the application was well accepted by the majority of the staff. We also showed that previous ICU working experience is independently and positively associated with compliance (p=0.02, OR=2.86; 95% CI: 1.16 - 7.06), after adjustment for age and total nursing experience In conclusion, we developed an effective application for quality improvement aiming at facilitating educational processes and enhancing staff compliance.